Rapid Maxillary Expansion and Facemask Therapy: Effects on Mandibular Condyle Position and Dentoskeletal Profile - Ahmet Yağcı; Tancan Uysal (Galenos Yayinevi, 2010)
Aim:The aim of this study was to evaluate the effects of the combination of rapid maxillary expansion and facemask therapy on mandibular condyle position and dentoskeletal profile; during the treatment of class III patients.Subjects and Methods:Treatment group comprised 31 patients, 16 girls and 15 boys (mean age: 9.2±1.7 years) and control group comprised 27 subjects, 14 girls and 13 boys (mean age: 9.7±2.2 years); with class III maxillary retrusion. Mandibular position indicator (MPI®) measurements of the SAM®3 articulator and cephalometric changes were evaluated. Treatment and control changes within the groups and the differences between the groups were analyzed statistically. Wilcoxon's paired sample test and Mann-Whitney U-test were used for statistical evaluation, at p<0.05 level.Results:At the start, more than 70 per cent subjects (range: 71.40-83.70 per cent) showed asymmetrical condylar movement in every plane of space. Significant change was determined in control group, for left condyle AZZ measurement, during observation period. Left AX change was found statistically higher in treatment group than the control (p<0.05). In the treatment group, SNB, U1-NA (mm) and U1-NA (degrees) measurements were decreased (p<0.05) and N-Me (p<0.05); SNA, SN-MP and ANS-Me (p<0.01); ANB, A to N perp and UL to E plane (p<0.001) measurements were increased, when compare to control.Conclusions:During the study period, left condyle anteroposterior position changed more and became closer to the centric relation position in the treatment group than the control. Rapid maxillary expansion and facemask therapy resulted in a significant improvement in the maxillomandibular relationship. Mandible moved downward and backward and maxilla moved forward direction without rotation.